ANALISIS PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (Studi pada Perusahaan Industri Manufaktur yang Go Public di Bursa Efek Indonesia Tahun 2011 - 2013) - Ailsa Devina Rahmasari, 12.05.51.0097; Sudiyatno, Bambang (Students Journal of Economic and Management, 2016)
This study attempts to test influences Debt to Equity Ratio, Return on Equity and Earning Per Share to the stock prices. This research was carried out on a go public industrial manufacturing company in Indonesia Stock Exchange. A method of the sample in this research using methods purposive sampling with a period of research in 2011 until 2013. The data used in this study is data from manufacturing companies that met the selection criteria. The analytical method used in this research is multiple regression analysis. The research proves that the DER have no significant negative effect on stock prices, ROE have no significant positive effect on stock prices, while EPS positive and significant effect on stock prices. Adjusted R Square value is 0845 it explains 84.5% of the dependent variable can be explained by the independent variable, while the remaining 15.5% is explained by other causes beyond the model. Keywords: Stock Prices, Debt to Equity Ratio, Return on Equity, Earnings Per Share